The IMF and Tax Reform. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
The paper deals with the activities of Fund staff with taxation. It is made up of four parts. Part I outlines the connection between Fund major activities and taxation. Part II surveys general influences on Fund staff with implications for tax work. Part III outlines the relationship between Fund-supported programs and changes in tax systems. Part IV focuses on the structure, rather than the level, of taxation. It outlines in broad terms the prevalent thinking of Fund staff on the structure of taxation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet